Insights and Reflections: ELT Trainee Teachers’ Experiences in Practicum - Pokhrel, Prem Raj; Kshetree, Arun Kumar (Butwal Campus Journal, 2024)
English language teachers’ practicum as a part of teacher education is one the learning strategies that helps the teachers to be professional. The main objective of the study was to explore the reflections and insights of the practicum for the trainee teachers in their teaching career. This study used a qualitative research design to explore how trainee teachers perceived their practicum, a required component of their degree program, and to learn how to teach. Four trainee teachers, purposefully chosen from four distinct Tribhuvan University campuses, participated in semi-structured interviews for data collection. The interviews were then transcribed, categorized, and analyzed using thematic terms. The study explored that the practicum encouraged the growth of trainee teachers and equipped them for the actual work and they saw it as a crucial instrument for learning to teach. The study also demonstrated that the practicum program was successful in fostering theory-practice connections, competency and confidence building, and socialization. The study also revealed that the trainee teachers' stressful experiences, inadequate resources, assessment-centered experiences, and a lack of support from supervisors and the school and college administration were the challenges to be addressed.